Nutrition Literacy and the Elderly with Hypertension - Pongkiatchai, Rungnapa; Wongwiseskul, Sresuda (Journal of Food Health and Bioenvironmental Science, 2018)
Hypertension is a highly prevalent condition with numerous health risks, and the incidence of hypertension is greatest among the elderly. There are a number of collateral effects, including risks for dementia, physical disability, cardiovascular, and diabetes. The multi-dimensional risks of hypertension among the elderly have been found to be associated with smoking, obesity, sedentary lifestyle and lack of physical activity. However, one of the determining factors of hypertension is food consumption. Consumption knowledge could help the elderly especially in a community setting. Being exposed to various types of health information influence elderly’s decision making, behavior changing and creating appropriate lifestyles; but knowledge alone cannot develop the skills for making the right consuming decision. Thus, why nutrition literacy intervention seek to be composed of both providing health information and types of empowering activities to ensure that the elderly can make their decision appropriately. Furthermore, those activities help them to develop critical thinking skills and lead to appropriate consumption decision when they share their successful experiences in their group.This article integrates the process of nutrition literacy by Nutbeam with the Sorensen model and relates them into practice management for the elderly with hypertension, no matter the elderly’s different level of knowledge or skills. At the end of this presentation, example of nutrition literacy intervention is provided to show that health education alone may be not enough to change the elderly mindset on consumption practice. In conclusion, nurses and health professionals should consider various types of activities for the elderly to sustain their behavioral changes.